Photoacoustic monitoring of tissue temperature at high temporal resolution - Upputuri, Paul Kumar (2019)
Monitoring of tissue temperature is necessary for guiding energy-based medical treatments. The local temperature information is also important for the safe deposition of light/heat energy into the surrounding healthy tissue. Existing imaging modalities fail to monitor tissue temperature with high accuracy and high resolution. Photoacoustic sensing of temperature was demonstrated using Q-switched Nd:YAG laser. A temperature sensitivity of ~0.15°C was obtained at a temporal resolution of ~2 s. Photoacoustic imaging is a high-speed, high-resolution, deep tissue imaging modality for both preclinical and clinical applications. In this work, we demonstrate photoacoustic sensing of temperature at high temporal resolution order of microseconds using high repetition rate (7000 Hz) near-infrared (~803 nm) pulsed laser diodes. The system will find applications in radiation therapy, photothermal therapy, photodynamic therapy, etc.